(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify: the effect of using the Baby model in achieving concepts in mathematics among middle school students. The problem is the existence of a large amount of mathematical concepts, laws, and generalizations in the content of the scheduled book and the weak interdependence between its chapters and scientific errors. Importance The intermediate stage is one of the important stages, as students are distinguished by the growth of their thinking, the strength of their memory and the stability of information in their minds for a longer period, as well as physical and mental changes That makes them not like students of the rest of the stages, so attention must be paid to their education using the teaching methods and methods that contribute to achieving the desired educational goals, as it has become necessary for schools to adopt a single goal of different dimensions and depths in the education stages, to enable learners to think methods, processes and patterns in their learning, according to Their maturity levels, the requirements of selected knowledge, and the characteristics of their communities. Research hypothesis: There is no statistically significant difference at the level (0,05) between the average scores of group (1) students that will be taught according to the Baby model and the average scores of group (2) students that will be taught in the usual way in the achievement test. The research found that group (1) students outperform group (1) students in mathematical concepts